The role of social assistance program on management accounting practice - Mira Fajrin Sholichatun; Hani Werdi Apriyanti (Journal of Islamic Accounting and Finance Research, 2021)
Purpose - The purpose of this study is to determine the procurement of social assistance program on management accounting practice of MSMEs in food industry sector in  Semarang during the Covid-19 pandemic.Method - The population in this study was 17,602 MSMEs in Semarang. The research samples were 144 MSMEs in the food industry sector in Semarang obtained using a non-random sampling technique with a purposive sampling method. The data were then processed using descriptive analysis, data quality test, classic assumption test, simple regression analysis, and hypothesis test with IBM SPSS 25 software.Result - The results show that procurement of social assistance program affected management accounting practice of MSMEs in the food industry sector in Semarang during the Covid-19 pandemic.Implication - The results show that with the support provided by the government and financial institutions in the form of social assistance programs to MSMEs had positive impacts by encouraging MSMEs to implement management accounting practices  during the covid-19 pandemic.Originality - Procurement of Social Assistance Program is an independent variable which is later expected to be able to overcome MSME problems due to the financing faced by MSMEs in Semarang in response to the impact of Covid-19 pandemic.